2020
DOI: 10.1109/tifs.2019.2946933
|View full text |Cite
|
Sign up to set email alerts
|

Extensible Conditional Privacy Protection Authentication Scheme for Secure Vehicular Networks in a Multi-Cloud Environment

Abstract: With an increasing number of cloud service providers (CSPs), research works on multi-cloud environments to provide solutions to avoid vendor lock-in and deal with the single-point failure problem have expanded considerably. However, a few schemes focus on the conditional privacy protection authentication of vehicular networks under a multi-cloud environment. In this regard, we propose a robust and extensible authentication scheme for vehicular networks to fulfil the evergrowing diversified service demands from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 54 publications
0
71
0
Order By: Relevance
“…It is not difficult to imagine that privacy is intertwined with security when communication networks are considered, and it is a well-established consensus that the IoV will be very vulnerable to a multitude of attacks (e.g. [4], [10], [11], [17], [32]- [34]). Security and privacy are vast topics, and this paper will focus explicitly on privacy in end-user services.…”
Section: Concerns About Privacy and Trust In The Iovmentioning
confidence: 99%
“…It is not difficult to imagine that privacy is intertwined with security when communication networks are considered, and it is a well-established consensus that the IoV will be very vulnerable to a multitude of attacks (e.g. [4], [10], [11], [17], [32]- [34]). Security and privacy are vast topics, and this paper will focus explicitly on privacy in end-user services.…”
Section: Concerns About Privacy and Trust In The Iovmentioning
confidence: 99%
“…Furthermore, the adversary can use oracle queries to interact with the entities. As far as we know, these two adversary models are widely adopted in the authenticated key exchange protocols [28].…”
Section: Reatmentioning
confidence: 99%
“…The user privacy should be preserved during authentication in VANET [5]. In order to hide the actual identities of the vehicles, the anonymity of vehicles is required for VANET.…”
Section: Introductionmentioning
confidence: 99%
“…The TA is also able to find the RSU who has authenticated the compromised vehicle by the traffic-related message that was sent from the compromised vehicle (4) The detailed security analysis demonstrated that the proposed vehicle authentication and the message verification protocol can not only resist various security threats but also have good security features, such as unforgeability of identity and message integrity (5) We evaluate the performance of the proposed authentication protocol and compare it with the related authentication protocols in terms of computation and transmission overheads. In addition, we also have analyzed the relationship between different factors and the message loss rate or the message delay of the authentication protocol…”
Section: Introductionmentioning
confidence: 99%